Education: The Heart of the Matter. (April 2018) - Morriss, Wayne W.; Milenovic, Miodrag S.; Evans, Faye M.
Abstract : There are inadequate numbers of anesthesia providers in many parts of the world. Good quality educational programs are needed to increase provider numbers, train leaders and teachers, and increase knowledge and skills. In some countries, considerable external support may be required to develop self-sustaining programs. There are some key themes related to educational programs in low- and middle-income countries: (1) Programs must be appropriate for the local environment—there is no "one-size-fits-all" program. In some countries, nonuniversity programs may be appropriate for training providers. (2) It is essential to train local teachers—a number of short courses provide teacher training. Overseas attachments may also play an important role in developing leadership and teaching capacity. (3) Interactive teaching techniques, such as small-group discussions and simulation, have been incorporated into many educational programs. Computer learning and videoconferencing offer additional educational possibilities. (4) Subspecialty education in areas such as obstetric anesthesia, pediatric anesthesia, and pain management are needed to develop leadership and increase capacity in subspecialty areas of practice. Examples include short subspecialty courses and clinical fellowships. (5) Collaboration and coordination are vital. Anesthesiologists need to work with ministries of health and other organizations to develop plans that are matched to need. External organizations can play an important role. (6) Excellent education is required at all levels. Training guidelines could help to standardize and improve training. Resources should be available for research, as well as monitoring and evaluation of educational programs.